The value orientation of entrepreneurs in challenging institutional contexts: Insights from a unique historical episode - Michael Wyrwich (Friedrich Schiller University Jena, 2020)
Previous research suggests that entrepreneurs value autonomy more than non-entrepreneurs do across countries and institutional contexts. However, most evidence exists for contexts with more or less entrepreneurship-facilitating and stable institutional frame-work conditions while we do not know whether this connection also exists in situations, in which entrepreneurs operate under challenging institutional conditions. This paper exploits a historical episode to first analyze a context where entrepreneurs faced massive institutional barriers and, second, a context marked by significant changes of the institutional framework conditions for entrepreneurship. In both contexts, entrepreneurs are challenged either by external resistance toward their activity or by uncertainty regarding the future prospects of their endeavor. Our results show an above-average endorsement of autonomy as an important societal value among people that were entrepreneurs in the autocratic anti-entrepreneurial regime and those respondents that started or planned to start an own venture during institutional upheaval. The findings of our analysis suggest that the mark-up entrepreneurs reveal with respect to valuing autonomy found in the previous literature is not an artefact of stable entrepreneurship-facilitating institutional framework conditions.
Keywords: L26; P20; Z10; 330; Entrepreneurship; Value orientation; Autonomy; Institutions